[tex]a)~3x -2 =x + 12[/tex]
[tex]3x - x = 12 + 2[/tex]
[tex]x=14:2[/tex]
[tex]2x=14[/tex]
[tex]x = 7[/tex]
[tex]b)~ -2x |3 - 5 |10 = 25x |100+ 2[/tex]
[tex]-2x | 3 - 1 |2 = x |4 + 2[/tex]
[tex]- 8x - 6 = 3x + 12[/tex]
[tex] 8x + 3x = -6 -12[/tex]
[tex]11x = - 18[/tex]
[tex]x = -18|11[/tex]
[tex]c)~ 7 * ( x -1) + 1 = -4 *( 3 -x )[/tex]
[tex] 7x - 7 + 1 = - 12 + 4x[/tex]
[tex] 7x - 7 + 1 = - 12 + 4x [/tex]
[tex]7x - 4x = - 12 + 6 [/tex]
[tex]3x = - 6 [/tex]
[tex] x = - 6 /3 [/tex]
[tex]x = - 3 [/tex]
[tex]d)~ 6 * ( 7 -2x ) = 5*( x +3) + 1 [/tex]
[tex]42 - 12x = 5x + 15 + 1 [/tex]
[tex] -12x - 5x = 16 - 42 [/tex]
[tex] - 17x = -26 [/tex]
[tex]x = 26 |17 [/tex]